The fateful journey : the expedition of Alexine Tinne and Theodor von Heuglin in Sudan (1863-1864) : a study of their travel accounts and ethnographic collections - Willink, Joost (Robert Joost), 1947- (Amsterdam University Press, 2011)
This compelling, richly illustrated work recounts the African journeys of the intrepid Dutch traveller Alexine Tinne (1835-1869). Heiress to a huge fortune -she was at the time the richest woman in the country - and bored with the royal court intrigues in The Hague, Tinne left for Egypt and Sudan accompanied by her mother Henriette Tinne-Van Capellen, ultimately settling in Khartoum. On her expedition in 1862-64, Tinne was joined by the German zoologist Theodor von Heuglin: the whole party set out for the as yet uncharted Bahr-el-Ghazal, hoping to explore that region and ascertain how far west.